The discourse vanishes: revolution and resilience in Indian politics ; review article - Mitra, Subrata Kumar (Contemporary South Asia, 2000)
Rezension von: Social change and political discourse in India. Structures of power, movements of resistance. / Ed. by T. V. Sathyamurthy. - Vol. 1-4. - 1994-1997